(untitled) (PYC Nepal Journal of Management, 2022)
This article discusses the outside-in approach to understanding human resource management (HRM) in relation to sustainable development goals (SDGs). The author presents four propositions, based on the literature review, that connect long-term business challenges to sustainable HRM goals. The article emphasizes the need for a wider scholarly and professional perspective in order to effectively conceptualize and implement sustainable HRM practices and address long-term business challenges. Due to the lack of sustainable HRM knowledge in countries like Nepal, the article aims to provide a detailed explanation of the concepts. As a conceptual paper, further expansion and testing of the propositions will be necessary in the future.